eleMENtary School:(Hyper) Masculinity in a Feminized Context - Richardson, Scott. author. aut Link
XII, 166 p.
Keywords: Scott Richardson gives us a finely detailed experiential account of how gender and teaching are woven together in public schools. Through his own memories and the narrativized experiences of his research subjects, Richardson demonstrates both the institutional benefits associated with being male and the fragility of masculinity. Membership in the “Boys’ Club” of hypermasculinity requires constant checking, surveillance, and choices that fit within the narrow range of dominant masculinity (so well detailed by R. W. Connell). Richardson’s causal style parallels the ease with which men in leadership and teaching positions articulate their allegiance to gender norms and one another, and in effect, set critique of such gender norms above comment: it’s just the way things are done. - Cris Mayo, Associate Professor of Education Policy, Organization and Leadership & Gender and Women’s Studies, University of Illinois at Urbana-Champaign; Faculty Director of the Odyssey Project; author of Disputing the Subject of Sex: Sexuality and Public School Controversies. Scott Richardson has written a provocative work that lifts the veil and explores a secret space hiding in plain sight in every school in America. The taboo is gender, and for teachers who often feel bound and gagged, unseen and unheard, Richardson’s efforts offer a life-altering experience that will change the way we understand classrooms. eleMENtary School: (hyper)masculinity in a Feminized Context is both forbidden fruit and a small masterpiece. - William Ayers, Distinguished Professor of Education and Senior University Scholar, University of Illinois at Chicago (retired); founder of the Center for Youth and Society; author of To Teach: The Journey of a Teacher, and co-author-editor of The Handbook of Social Justice in Education with T. Quinn & D. Stovall. eleMENtary School tells the important and untold story of teachers’ enactments of normative masculinity. Through vivid and compellingaccounts of male teachers like Dru, Alex and Owen we learn about how contemporary definitions of masculinity prevent teachers from fulfilling their potential as educators, as colleagues and as role models. Only by reading carefully a documented analysis like these can we begin to critically examine the way in which we can encourage male teachers to develop what Scott Richardson calls an “ethic of care,” that supports gender equality, rather than allowing them to continue to engage in damaging practices of normative masculinity. - CJ Pascoe, Assistant Professor of Sociology; author of Dude You’re a Fag: Masculinity and Sexuality in High School and Anas, Mias and Wannas: Identity and Community in a Pro-ana Subculture. Scott Richardson's eleMENtary School: (hyper)masculinity in a Feminized Context is a remarkable innovative contribution to teacher lore, narrative inquiry, and gender studies. Readers cannot experience this book without pondering, questioning, rethinking, and reconstructing their perspective on education and its socio-sexual and political milieu. Surely, that is one of the most laudable consequences of a scholarly contribution in education. I urge educators at all levels to let this book have impact on their outlooks. - William H. Schubert, Professor Emeritus, Dept. of Curriculum & Instruction, University of Illinois at Chicago; former Director the Teacher Lore Project; co-author-editor of Teacher Lore: Learning from Our Own Experience with W. Ayers, and author of Love, Justice and Education. Scott Richardson is an Assistant Professor of Educational Foundations, Women’s Studies faculty member, and co-founder of the Sexuality & Gender Institute at Millersville University.